General Considerations around the Understanding of the Reality of the Social World - Chinche Calizaya, Saul Marcelo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2020)
The construction of knowledge in the Social Sciences, undoubtedly has an unfinished character given its provisional nature; It is clear that there is always something radically incomplete in this type of knowledge, whose study is precisely oriented to the analysis of social phenomena. We arrive at this statement, by virtue of the fact that social phenomena in general tend to resemble unrepeatable periodicities not only because of their actors who interact in it, but basically because of the delimitation of time-space; added to the fact that they are unstable, complex, dynamic and contradictory, which make it even more difficult to understand and interpret them.